A CONCEPTUAL STUDY ON FINANCIAL WELL-BEING AMONG MICRO-ENTREPRENEURS - Noor Inani Che Aziz; Wan Farha Wan Zulkiffli; Hazriah Hasan (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
Purposes: In Malaysia, micro, small and medium-sized enterprises (MSMEs) which are dominantly micro-enterprises owned by micro-entrepreneurs (MEs), were facing among the greatest risks to financial security in the midst of the current post-COVID-19 era. MEs’ financial situation is at an alarming level, and they need help to increase their financial well-being (FWB). Therefore, it is crucial to understand that group in the FWB study. Among the issues that they face are competition among their counterparts, difficulty in adapting to the current business landscape, which is digital business and the rising cost of living, worsening it by elevating the main problem in MEs, “financial resources”. Therefore, the paper aims (1) to identify major current issues/ factors that contribute to FWB of MEs in Malaysia by extensively reviewing current past literature and (2) to propose a framework that includes predictors of FWB in MEs’ “context”. Methodology: The study reviewed past literature related to FWBs that mainly focused on journal articles from the year (2020 to 2024) primarily using Scopus and Google Scholar databases. Results: Findings from the study included (1) the factors that contributed to FWB, consisting of psychological factors, financial literacy, and financial management practices; and (2) a framework was proposed pertaining to the study. Conclusion: The current study helps to the development of FWB’s framework. According to the findings, it appears that future studies can focus more on the study of MEs’ FWB as the group was very fragile and needs more help in addition to the limited study of the group in FWB’s “context”, especially in developing countries like Malaysia.